MDI 301, a synthetic retinoid, depressed levels of matrix metalloproteinases and oxidative stress in diabetic dermal fibroblasts - Zhai, Jianhua (Oncotarget, 2017)
Diabetic foot ulcerations could result in serious consequences such as amputations. The up-regulation of matrix metalloproteinases and down-regulation of TIMP1 were remarked as distinctive biological characteristics in the diabetic dermal fibroblast. The current study was performed in order to clarify the effect of high glucose on formation of diabetic dermal fibroblast cell. In addition, the effect of MDI 301 on ameliorating diabetic fibroblasts was investigated in this study. The mRNA and protein expression levels of MMPs, TIMP1 and catalase were evaluated against fibroblasts treated with high glucose (30 mM) using qRT-PCR, western blotting and zymography assays. Methods were also employed for investigating the biological effects of MDI 301 on high glucose-induced diabetic fibroblasts. In this study, we found that the unbalance of oxidative stress induced by high glucose concentration play an important role in the formation of diabetic dermal fibroblast from normal cells. In addition, MDI 301, a picolinic acid-substituted ester of 9-cis retinoic acid was employed in this study in order to ameliorate symptoms on diabetic dermal fibroblast induced by high glucose concentration. We found MDI 301 alleviate the effects of high glucose-induced skin damage by balancing the oxidative stress and regulating the MMPs and TIMP1 levels. Our finding indicated that MDI 301 offers the potential for repairing the faulty skin function arising from diabetes.